Preparation of graphene on Cu foils by ion implantation with negative carbon clusters - 李慧 尚艳霞 张早娣 王泽松 张瑞 付德君 (Chinese physics B, 2015)
We report on few-layer graphene synthesized on Cu foils by ion implantation using negative carbon cluster ions,followed by annealing at 950？C in vacuum. Raman spectroscopy reveals IG/I2 Dvalues varying from 1.55 to 2.38 depending on energy and dose of the cluster ions, indicating formation of multilayer graphene. The measurements show that the samples with more graphene layers have fewer defects. This is interpreted by graphene growth seeded by the first layers formed via outward diffusion of C from the Cu foil, though nonlinear damage and smoothing effects also play a role. Cluster ion implantation overcomes the solubility limit of carbon in Cu, providing a technique for multilayer graphene synthesis.